Preparação de 1,1,1-trialo-4-metil[fenil]seleno-3-alquen-2-onas como precursores para síntese de 3-trialometil-[3-carboxi] isoselenazóis - Bastos, Giovani Palma (2002)
A convenient synthesis of 16 1,1,1-trihalo-4-methyl[phenyl]seleno-3-alken-2-ones [CX3C(O)CH=CR1SeR, where X = Cl, F; R = Me, Ph e R1 = H, Me, Et, n-Pr, iso-Pr, iso-Bu, Ph, 4-F-C6H4 e 4-Cl-C6H4], from the reaction of the corresponding 1,1,1-trihalo-4-methoxy-3-alken-2-ones with selenium nucleophilic in presence of boron trifluoride etherate, is reported. The reaction of the 1,1,1-trihalo-4-methyl[phenyl]seleno-3-alken-2-ones with bromine and ammonia to –700C furnished the of 3-trihalomethyl isoselenazoles in good yelds ( 68 – 81% ). The reaction of 3-trihalomethyl isoselenazoles in sulfuric acid and water as solvent, lead to the isoselenazoles carboxilic acids ( 70 – 80% ), while the reaction of the 3-trihalomethyl isoselenazoles in sulfuric acid and methanol as solvent lead to the respective methoxicarbonylselenazoles, in good yelds, ( 71 – 75% ), with the transformation of the CCl3 into CO2R2.